An update on the genetics of benign pituitary adenomas in children and adolescents - Hannah-Shmouni, Fady (Curr Opin Endocr Metab Res, 2018)
Pituitary adenomas in children and adolescents are rare tumors that often result from a tumor predisposition syndrome. Several inherited causes for pituitary adenomas have been identified in the last few years, including multiple endocrine neoplasia type 1 and 4, Carney’s complex, Tuberous sclerosis, DICER1 syndrome, neurofibromatosis type 1, McCune Albright syndrome, familial isolated pituitary adenoma, and pituitary adenoma association due to defects in succinate dehydrogenase genes. Recently, our group discovered X-linked acrogigantism (X-LAG), a new pediatric disorder that is caused by an Xq26.3 genomic duplication (involving the GPR101 gene). Genes that predispose to pediatric Cushing disease, including CABLES1 and USP8, were also recently identified. Genetic screening and counseling of affected or at risk individuals is a key component of their comprehensive care. In this review, we provide an up-to-date discussion on the latest pediatric genetic discoveries associated with pituitary adenomas with a focus on familial syndromes.